Comparison of Total Bacterial Count in Contact Lenses with Different Treatments of Contact Lens Solutions - Husna, Hanna Nurul; Virgianti, Dewi Veti; Lestari, Sindiyani Wini (JURNAL INFO KESEHATAN, 2024)
The use of contact lenses continues to increase, raising attention to aspects of eye health because of their hygienic factors. The hygiene of contact lenses comes not only from the way they are treated but also from the soaking fluid. This study aimed to determine the total bacterial count on contact lenses with and without the use of immersion solutions. The research method used is a comparative descriptive research method that compares the two pairs of contact lenses with two different contact lens solutions. The total bacterial count was calculated using the total plate count (TPC) method. The number of bacterial colonies for contact lenses before being immersed in liquid A was found in dilution 10-2 with an amount of 4.4×103 CFU/mL, and after soaking, it was in dilution 10-1 with an amount of 8.5×102 CFU/mL. The number of bacterial colonies on contact lenses before being immersed in B liquid was found in 10-1 dilution with an amount of 1.3×103 CFU/mL, and after being soaked, the average colony was 3.9×104 CFU/mL. From these results, it can be seen that in contact lenses and liquid A, there is a decrease in the number of bacterial colonies, while on the other hand, in liquid B, there is an increase in the number of bacterial colonies. The causal factor is thought to originate from the composition of the solutions. However, do not rule out contamination from bottles and contact lens care. Therefore, this research can be used as a basis for hygiene education in contact lenses.